2008
DOI: 10.1007/s10162-008-0145-8
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to Interaural Time Differences with Combined Cochlear Implant and Acoustic Stimulation

Abstract: The interaural time difference (ITD) is an important cue to localize sound sources. Sensitivity to ITD was measured in eight users of a cochlear implant (CI) in the one ear and a hearing aid (HA) in the other severely impaired ear. The stimulus consisted of an electric pulse train of 100 pps and an acoustic filtered click train. Justnoticeable differences (JNDs) in ITD were measured using a lateralization paradigm. Four subjects exhibited median JNDs in ITD of 156, 341, 254, and 91 μs; the other subjects could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
102
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 56 publications
(109 citation statements)
references
References 28 publications
7
102
0
Order By: Relevance
“…Additionally, response latencies for EASSRs should be smaller than for comparable acoustic stimuli because of the direct excitation of the nerve. A comparison between wave V latencies of 4.20 ms for EABRs to basal stimulation (Shallop et al 1990) and 5.64 ms for ABRs (Nikiforidis et al 1993) shows a difference of about 1.4 ms, while the necessary delay of the electric pathway for psychoacoustically synchronous bimodal stimulation is about 1.5 ms (Francart et al 2009).…”
Section: Response Amplitudesmentioning
confidence: 95%
“…Additionally, response latencies for EASSRs should be smaller than for comparable acoustic stimuli because of the direct excitation of the nerve. A comparison between wave V latencies of 4.20 ms for EABRs to basal stimulation (Shallop et al 1990) and 5.64 ms for ABRs (Nikiforidis et al 1993) shows a difference of about 1.4 ms, while the necessary delay of the electric pathway for psychoacoustically synchronous bimodal stimulation is about 1.5 ms (Francart et al 2009).…”
Section: Response Amplitudesmentioning
confidence: 95%
“…They were selected to have residual hearing thresholds better than 100-dB sound pressure level (SPL) at 1,000 and 2,000 Hz, since we found previously that this was related to good ITD sensitivity (Francart et al 2009). They were volunteers and signed an informed consent form.…”
Section: Subjectsmentioning
confidence: 99%
“…In our previous studies assessing interaural time difference (ITD) perception with bimodal hearing (Francart et al 2009 we have found ITD sensitivity in the envelope of simple synthetic singleand three-channel stimuli. For multiple-channel stimuli, ITD sensitivity was found when the electrical signal contains deep modulations that are consistent across different channels (electrodes).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations